2010
DOI: 10.1021/jp109620b
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Nonclassical Content of Clathrate Hydrates Through the Choice of Molecular Guests and Temperature

Abstract: Low-temperature, low-pressure studies of clathrate hydrates (CHs) have revealed that small ether and other proton-acceptor guests greatly enhance rates of clathrate hydrate nucleation and growth; rapid formation and transformations are enabled at temperatures as low as 110 K, and cool moist vapors containing small ether molecules convert to mixed-gas CHs on a subsecond time scale. More recently, FTIR spectroscopic studies of the tetrahydrofuran (THF)-HCN double clathrate hydrate revealed a sizable frequency sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 34 publications
3
32
0
Order By: Relevance
“…The assignments follow from (1) loss of the 1033 band (blue spectrum) during replacement of MeOH by DME as the largecage guest, and (2) a fading of the 1017 cm −1 band as CO 2 partially displaces MeOH from the small cages during equilibration over time with 80 Torr of CO 2 gas at 170 K. The extra width of these MeOH CO stretch bands (∼18 cm −1 ) is consistent with previous reports for MeOH and other guest molecules H-bonded with cage walls. 3,24,25 Bands of the hydrate CO 2 asymmetric stretch mode are hidden by gas-phase saturation of absorption in the 2340 cm −1 region of the spectrum so, as previously, 20 the loading of CO 2 that depleted the MeOH small-cage population in the inset of Fig. 2 was followed using the weak in-tensity of the 3703 cm −1 band of the combination mode (not shown).…”
Section: A Mixed Meoh-co 2 Chs (∼100%) From Vapor Pre-mixtures Of Wamentioning
confidence: 62%
See 3 more Smart Citations
“…The assignments follow from (1) loss of the 1033 band (blue spectrum) during replacement of MeOH by DME as the largecage guest, and (2) a fading of the 1017 cm −1 band as CO 2 partially displaces MeOH from the small cages during equilibration over time with 80 Torr of CO 2 gas at 170 K. The extra width of these MeOH CO stretch bands (∼18 cm −1 ) is consistent with previous reports for MeOH and other guest molecules H-bonded with cage walls. 3,24,25 Bands of the hydrate CO 2 asymmetric stretch mode are hidden by gas-phase saturation of absorption in the 2340 cm −1 region of the spectrum so, as previously, 20 the loading of CO 2 that depleted the MeOH small-cage population in the inset of Fig. 2 was followed using the weak in-tensity of the 3703 cm −1 band of the combination mode (not shown).…”
Section: A Mixed Meoh-co 2 Chs (∼100%) From Vapor Pre-mixtures Of Wamentioning
confidence: 62%
“…25 The joint action with MeOH, as with DME, parallels that described for THF with HCN wherein the small-cage HCN enhances the non-classical character by stabilizing the cage-wall H 2 O as O-H bonding is switched to the oxygen of the THF. 12,24 That is, like for HCN, an acid end of C 2 H 2 H-bonds with oxygen of the cage walls producing a sizable shift of the C 2 H 2 asymmetric C-H stretch mode.…”
Section: Comparison Of the Effect Of The Small-cage Help Gases Acementioning
confidence: 70%
See 2 more Smart Citations
“…Pure ammonia clathrate hydrate synthesis cannot be done by simply cooling aqueous ammonia solutions, as a variety of stoichiometric hydrates of ammonia are known to form preferentially (2,11,18,19). Other ways of forming clathrate hydrates include vapor deposition of water at low temperatures to yield amorphous ice, followed by exposure of the ice to a pressure of guest gas and annealing (29), or vapor codeposition of water and the potential guest material at low temperatures, again, followed by annealing (23,30,31). It has been shown that below approximately 140 K ice surfaces are relatively inert unless strong hydrogen-bond donors or acceptors are present.…”
Section: Resultsmentioning
confidence: 99%